2003
DOI: 10.1046/j.1460-9568.2003.02859.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DARPP‐32 Thr75 phosphorylation by neurotensin in neostriatal neurons: involvement of glutamate signalling

Abstract: Neurotensin is a neuropeptide involved in dopaminergic signalling. We have recently reported that neurotensin stimulates the phosphorylation of DARPP-32 (dopamine- and cAMP-regulated phosphoprotein of Mr 32 kDa) at Thr34 (PKA-site) by activating dopamine D1-type receptors in neostriatal neurons. DARPP-32 is also phosphorylated by cyclin-dependent kinase 5 on Thr75, and the phosphorylated form of DARPP-32 at Thr75 inhibits protein kinase (PKA) activity. In this study, we examined the effect of neurotensin on DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…We observed that NT inhibits glutamatergic transmission in the dorsolateral striatum, probably by reducing presynaptic glutamate release, since the observed reduction in EPSC amplitude was accompanied by an increase in PPR, an indication of reduced presynaptic release probability (Figure 2A). This is a new and somewhat surprising observation, as most previous neurochemical studies found that NT either increases the release of transmitters like dopamine and glutamate in the striatum (Okuma et al, 1983;Battaini et al, 1986;Hetier et al, 1988;Ferraro et al, 1995;Ferraro et al, 1998;Diaz-Cabiale et al, 2002;Matsuyama et al, 2002;Matsuyama et al, 2003) or increases the excitability of the postsynaptic cell in substantia nigra and medial septum/diagonal band of Broca (Mercuri et al, 1993;Matthews, 1999). By blocking the NT-induced inhibition of striatal EPSCs with the NTS1 receptor antagonist SR 142948 (Gully et al, 1997), we showed that this effect on glutamatergic transmission depends on the activation of NTS1 receptors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We observed that NT inhibits glutamatergic transmission in the dorsolateral striatum, probably by reducing presynaptic glutamate release, since the observed reduction in EPSC amplitude was accompanied by an increase in PPR, an indication of reduced presynaptic release probability (Figure 2A). This is a new and somewhat surprising observation, as most previous neurochemical studies found that NT either increases the release of transmitters like dopamine and glutamate in the striatum (Okuma et al, 1983;Battaini et al, 1986;Hetier et al, 1988;Ferraro et al, 1995;Ferraro et al, 1998;Diaz-Cabiale et al, 2002;Matsuyama et al, 2002;Matsuyama et al, 2003) or increases the excitability of the postsynaptic cell in substantia nigra and medial septum/diagonal band of Broca (Mercuri et al, 1993;Matthews, 1999). By blocking the NT-induced inhibition of striatal EPSCs with the NTS1 receptor antagonist SR 142948 (Gully et al, 1997), we showed that this effect on glutamatergic transmission depends on the activation of NTS1 receptors.…”
Section: Discussionmentioning
confidence: 88%
“…As NT is often thought to increase glutamate release in the striatum (Matsuyama et al, 2003), our observation that it inhibits striatal EPSCs via retrograde endocannabinoid signaling is surprising. There are three possible mechanisms for the observed effect: 1) enhanced glutamate release activating extrasynaptically located group I mGluRs; 2) direct activation of the G q -coupled NTS1 on dendrites and soma of MSNs, with a consequent increase in intracellular calcium; and 3) enhanced dopamine release activating postsynaptic D2 receptors.…”
Section: Possible Mechanisms For Nt-induced Inhibition Of Epscsmentioning
confidence: 86%
“…Similar in vivo and in vitro studies indicate the enhancing effects of NT on endogenous glutamate [98,99,100,101,102]. The perfusion of NT in the NA is thought to activate NTS1 receptors located on accumbal glutamate terminals, thereby inducing an enhancement of glutamate outflow that could be associated with a concomitant and significant reduction in accumbal dopamine release [103].…”
Section: Neurotensin and Schizophreniamentioning
confidence: 97%
“…In the cultured cortical neurons model, glutamate exerts exocytotoxicity via N -methyl-D-aspartate (NMDA) receptors, leading to an apoptotic cell death [61]. It has been shown that NT significantly enhances glutamatergic signaling, both in vitro and in vivo , by increasing glutamate release [62,63,64,65]. The fact that the cerebral level of NT increases following ischemia [66] could suggest an involvement of the peptide in ischemic brain damage.…”
Section: Pro-apoptotic Action Of Nt In the Central Nervous Systemmentioning
confidence: 99%